Developing 2D Animation with a Lateral Thinking Theme Using Facial Motion Capture - Yahya, Saiful; Eliansah, Ivan; Adisusilo, Anang Kukuh; Kusumasari, Adita Ayu (Universitas Pendidikan Indonesia (UPI), 2024)
Lateral thinking is the ability to think critically using unconventional thought patterns, crucial for problem-solving. This study explores the use of 2D animation as a visual communication medium to convey lateral thinking concepts. By employing facial motion capture technology, the animation production process was accelerated and simplified. A 2D animation prototype was developed and evaluated with 25 undergraduate students in the field of design through a comprehension test and survey. Results showed that 90% of respondents understood the lateral thinking concept after viewing the animation. These findings demonstrate that facial motion capture is proved effective in optimizing the production process of 2D Animations by reducing manual effort in facial animation. This research contributes to the field of visual communication by integrating innovative animation technologies for educational purposes. Future studies should further explore the application of facial motion capture in creating educational 2D animations on STEM (Science, Technology, Engineering and Mathematics ) and other interdisciplinary themes.